A novel assay for the identification of NOTCH1 PEST domain mutations in chronic lymphocytic leukemia - Campregher, PV; Petroni, RC; Muto, NH; Sitnik, R; de Carvalho, FP; Bacal, NS; Velloso, EDRP; Oliveira, GB; Pinho, JRR; Torres, DC; Braga Mansur, M; Hassan, R; et al. (Hindawi Publishing Corporation, 2016)
Aims. To develop a fast and robust DNA-based assay to detect insertions and deletions mutations in exon 34 that encodes the PEST domain of NOTCH1 in order to evaluate patients with chronic lymphocytic leukemia (CLL). Methods. We designed a multiplexed allele-specific polymerase chain reaction (PCR) combined with a fragment analysis assay to detect specifically the mutation c.7544_7545delCT and possibly other insertions and deletions in exon 34 of NOTCH1. Results. We evaluated our assay in peripheral blood samples from two cohorts of patients with CLL. The frequency of NOTCH1 mutations was 8.4% in the first cohort of 71 unselected CLL patients. We then evaluated a second cohort of 26 CLL patients with known cytogenetic abnormalities that were enriched for patients with trisomy 12. NOTCH1 mutations were detected in 43.7% of the patients with trisomy 12. Conclusions. We have developed a fast and robust assay combining allele-specific PCR and fragment analysis able to detect NOTCH1 PEST domain insertions and deletions.